Adjuvant radiation therapy for male breast cancer: a rare indication? - Forster, Tobias; Köhler, Clara; El-Shafie, Rami; Weykamp, Fabian; König, Laila; Arians, Nathalie; Adeberg, Sebastian; Michel, Laura L.; Smetanay, Katharina; Golatta, Michael; Sohn, Christof; Heil, Jörg; et al. (Cancers, 2020)
Due to its rarity, there are no randomized trials investigating the outcome of adjuvant radiotherapy in MBC. This study reports on patient and tumor characteristics of 41 consecutive MBC patients treated between 1990 and 2018 and on clinical outcomes after surgical resection of tumors and adjuvant radiotherapy of the chest wall or breast. Local control (LC), locoregional control (LRC), overall survival (OS), disease-free survival (DFS), and toxicity were evaluated. After a median follow-up of 80 months (95% CI: 14.6–213.8 months) there was only one recurrence, in a patient’s locoregional lymph nodes 17 months after start of radiotherapy, resulting in an LC rate of 100% at 5 years and a 5-year LRC rate of 97.4% (standard deviation (SD): 0.025). Five-year DFS and OS rates were 64.6% (SD: 0.085) and 57.2% (SD: 0.082), respectively. Adjuvant radiotherapy was tolerated well without high-grade (CTCAE grade > II) adverse events. After tumor resection and adjuvant radiotherapy, LC and LRC rates in MBC patients are excellent and comparable to results found for female breast cancer (FBC) patients. However, as patients are often diagnosed with locally advanced, higher-risk tumors, distant recurrences remain the major failure pattern.
Gesehen am 03.03.2022